A new k‐epsilon model consistent with Monin–Obukhov similarity theory. Issue 3 (3rd August 2016) - van der Laan, M. Paul; Kelly, Mark C.; Sørensen, Niels N.
Abstract: A new k ‐ ϵ model is introduced that is consistent with Monin–Obukhov similarity theory (MOST). The proposed k ‐ ϵ model is compared with another k ‐ ϵ model that was developed in an attempt to maintain inlet profiles compatible with MOST. It is shown that the previous k ‐ ϵ model is not consistent with MOST for unstable conditions, while the proposed k ‐ ϵ model can maintain MOST inlet profiles over distances of 50km. Copyright © 2016 John Wiley & Sons, Ltd.